Impact of the COVID-19 Pandemic on the Implementation of Online Learning Students of SMP Negeri 3 Rambipuji Jember - Endri Setyoningrum; Mohamad Na’im; Sukidin Sukidin (Publikasi Indonesia, 2022)
The temporary closure of educational institutions in an effort to prevent the spread of COVID 19 has an impact on millions of students, including in Indonesia. The purpose of the study was to determine the impact of the COVID 19 pandemic on the online learning process for students of SMP Negeri 3 Rambipuji. In this study, the author uses qualitative research methods with the type of case study research. Data collection techniques using observation, interviews and documentation. The results show that online learning is a solution in teaching and learning activities during the COVID-19 pandemic. Online learning is learning that uses the internet network with accessibility, connectivity, flexibility and the ability to bring up various types of learning interactions. In the implementation of online learning, educators use the WhatsApp and Google Classroom applications. The results of the research and discussion found that the impact of COVID 19 on the implementation of online learning at SMP Negeri 3 Rambipuji was not effective.